The Effect of Debt to Equity Ratio and Return On Asset on Dividend Payout Ratio with Firm Size as a Moderating Variable in Manufacturing Companies on the Indonesia Stock Exchange - Anisa, Disa Ulan; Sobarsyah, Muahammad; Nohong, Mursalim (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2023)
The dividend payment policy is one of the important decisions in a company's financial management, especially in terms of returns to shareholders. This study aims to examine the effect of Debt-to-Equity Ratio (DER) and Return on Assets (ROA) on Dividend Payout Ratio (DPR) with Firm Size as a moderation variable. The data used is manufacturing companies listed on the Indonesia Stock Exchange during the 2019-2023 period. Hypothesis testing was carried out using SPSS. The population in this study was obtained with the number of manufacturing companies as many as 165 companies. The results show that DER and ROA have a significant effect on the DPR, but Firm Size does not moderate the relationship. This research contributes to understanding the influence of capital structure and profitability on the company's dividend policy in the manufacturing sector